The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/cmi.12271
|View full text |Cite
|
Sign up to set email alerts
|

An L2 SUMO interacting motif is important for PML localization and infection of human papillomavirus type 16

Abstract: SummaryHuman papillomaviruses (HPV) induce warts and cancers on skin and mucosa. The HPV16 capsid is composed of the proteins L1 and L2. After cell entry and virus disassembly, the L2 protein accompanies the viral DNA to promyelocytic leukaemia nuclear bodies (PML-NBs) within the host nuclei enabling viral transcription and replication. Multiple components of PML-NBs are regulated by small ubiquitin-like modifiers (SUMOs) either based on covalent SUMO modification (SUMOylation), or based on non-covalent SUMO i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 94 publications
3
56
0
Order By: Relevance
“…HPV16, -18, and -31 pseudoviruses (PsVs) and HPV16 L1-only PsV were prepared as previously described and published (33,53,64). Quantification of the reporter gene plasmid was performed as published before (28,53,65).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HPV16, -18, and -31 pseudoviruses (PsVs) and HPV16 L1-only PsV were prepared as previously described and published (33,53,64). Quantification of the reporter gene plasmid was performed as published before (28,53,65).…”
Section: Methodsmentioning
confidence: 99%
“…Fixed cells were washed three times with PBS and blocked for 30 min with PBS-1% (wt/vol) bovine serum albumin (BSA; AppliChem, Darmstadt, Germany). For L2 staining after PsV exposure, cells were incubated with Click-iT reaction cocktail according to the manufacturer's instructions (without the addition of EdU label for PsV staining) as described previously (22,53). Afterwards, proteins were stained with the desired antibodies at 37°C for 1 h. After washing with PBS, coverslips were blocked with PBS-1% BSA for 10 min and subsequently incubated with Alexa-conjugated specific secondary antibodies or phalloidin-tetramethyl rhodamine isothiocyanate (TRITC; Sigma-Aldrich, St. Louis, MO) for 1 h at 37°C in the dark.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several viruses relocate viral proteins into ND10 bodies to enhance their replication. Thus, SV-40 large T antigen colocalizes with PML and ND10 bodies, and papillomavirus minor capsid protein L2 colocalizes with PML and ND10 (24)(25)(26). It has been reported that one component of ND10, SP100, provides intrinsic immunity against papilloma viruses (27).…”
mentioning
confidence: 98%
“…Using this approach, Greber and co-workers succeeded to produce progeny Ad virions containing labeled genomes and to visualize single genomes of incoming viruses in early phases of infection [29]. This technique has also been used for visualizing incoming genomes of other viruses such as HSV-1 and papillomavirus [30,31,32]. To produce genome-labeled viruses, one may need to test several analogs, since labeling efficiency as well as cellular/viral toxicity varies among them.…”
Section: Experimental Strategies To Study Nuclear Antiviral Factorsmentioning
confidence: 99%